Fauna and its relation to edaphic attributes in Lages, Santa Catarina - Brazil Fauna e sua relação com atributos edáficos em Lages, Santa Catarina - Brasil - Pompeo P.N.* (2016)
The soil fauna is sensitive to environmental disturbances, their response may indicate the state of soil conservation in different uses and management practices. The aim of this study was to evaluate the diversity of invertebrate fauna groups and its relationship with edaphic attributes in three land uses: Native Forest (NF), Pinus Reforestation (PR) and Native Improved Grassland (NIM), in Lages, SC - Brazil. Sampling consisted of three points distanced each other 30 meters, established along transects, on each system. The evaluations were physical and chemical soil attributes and the abundance and diversity of fauna, collected by methods Pitfall traps and Tropical Soil Biology and Fertility. The data were subjected to multivariate statistical analysis. They identified 1.210 soil organisms belonging to 17 taxonomic groups. The most representative groups were Collembola and Coleoptera, independent of the use. The NF has introduced greater richness and diversity of soil fauna in comparison to other LUS. The highest levels of organic matter and soil pH showed a relationship with Oligochaeta, Enchytraeidae and Collembola. The values of moisture contributed to explain the greater abundance of groups in NIM and NF. However, the soil fauna showed different responses in its distribution to each land use, being that the environmental variables may limit the establishment of most frequent belowground invertebrates. NF systems and NIM presented better terms of edaphic attributes and therefore greater biodiversity, when compared to the PR.